Wnt Signaling Pathway in Uterus of Normal and Seminal Vesicle Excised Mated Mice during Pre-implantation Window - Latifi, Zeinab; Fattahi, Amir; Hamdi, Kobra; Ghasemzadeh, Aliye; Karimi, Pouran; Nejabati, Hamid Reza; Novin, Marefat Ghaffari; Roshangar, Leila; Nouri, Mohammad (Geburtshilfe und Frauenheilkunde, 2018)
Introduction The importance of seminal vesicle secretion and uterine Wnt signaling for uterus preparation and embryo implantation has been described.Materials and Methods In this study, we evaluated the gene expression of Wnt ligands (Wnt4 and Wnt5a) and their corresponding receptors (Fzd2 and Fzd6) using qRT-PCR and active β-catenin protein levels using western blotting in the uterine tissue of female mice mated with intact and seminal vesicle-excised (SVX) males during the pre-implantation window. We evaluated the association between these factors and implantation rates and embryo spacing.Results mRNA expression of Wnt4 and Wnt5a and active β-catenin protein levels decreased from Day 1 to Day 4, but reached a peak on the fifth day of pregnancy. Fzd2 also reached its highest level on Day 5. Fzd6 expression showed a decreasing trend towards the day of implantation. Lack of seminal vesicle secretion decreased Wnt4 and Wnt5a expression on Days 1 and 5 and β-catenin levels on Day 5. There were almost no significant differences in expression levels of the Fzd2 and Fzd6 receptors between groups. There were positive and negative correlations, respectively, between implantation rates and embryo spacing and Wnt4, Wnt5a and active β-catenin in the control group, but such correlations were not observed in the SVX-mated mice.Conclusions Significant changes occurred in the expression of several Wnt signaling members and there was a significant association between Wnt signaling and embryo implantation. Seminal vesicle secretion affects Wnt signaling in mice and consequently also affects murine embryo implantation.
Keywords: Wnt signaling; embryo implantation; seminal fluid; decidualization